Development of Ozone prediction model in urban area - Abdullah S.; Nasir N.H.A.; Ismail M.; Ahmed A.N.; Jarkoni M.N.K. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
One of the main challenges for countries in tropical area such as Malaysia is the high concentration of ozone (O3) caused by elevated levels of anthropogenic and natural ozone precursors. In this study, variation of O3 concentrations in urban area (Klang) was investigated using data covering three-year period (20122015) on hourly basis. Result shows that the diurnal cycle of ozone concentration has a mid-day peak (1400hrs) while lower concentration occurs at night time (2100hrs) as it titrates nitrogen dioxide (NO2). There exists statistically significant difference (p<0.05) of O3 concentration at study areas. Moderate Spearman correlation coefficient was evaluated between O3 and NO2 (r=0.45, p<0.05). Multiple linear regression (MLR) model was developed and signifies that nitrogen oxides (NO), relative humidity (RH), NO2, carbon monoxide (CO), wind speed (WS), temperature (T) and sulphur dioxide (SO2) are the significant predictors for O3 concentration. This study suggests that the emission of O3 precursors, particularly NOx from motor vehicles, needs to be controlled to reduce the incidence of high O3 levels in Malaysia. BEIESP.